Apolipoprotein C-III, a strong discriminant of coronary risk in men and a determinant of the metabolic syndrome in both genders - Onat, A; Hergenç, G; Sansoy, V; Fobker, M; Ceyhan, K; Toprak, S; Assmann, G (ELSEVIER IRELAND LTD, 2003)
Aims: Apolipoprotein C-III (apoC-III) has been recognized as a useful marker of triglyceride-rich lipoproteins (TRLs) metabolism and proposed as an indicator of prognosis for coronary risk in healthy subjects. We studied cross-sectionally in a population having low cholesterol levels, but a high prevalence of the metabolic syndrome, whether serum levels of total apoC-III or its sub-fractions were independent markers of prevalent coronary heart disease (CHD) or were related to variables reflecting the metabolic syndrome. Methods and results: In 857 unselected participants of the representative population sample of the Turkish Adult Risk Factor Survey in 2001, apoC-III as well as other risk variables were evaluated, and CHD was diagnosed based on clinical findings and Minnesota coding of resting electrocardiograms. The sample consisted of men and women, aged 33-82 years, having a mean waist circumference of 89.4 and 92.9 cm, respectively, 42% of whom had the metabolic syndrome identified by criteria of the ATP III. ApoG-III values were measured by turbidimetric immunoassay. Mean concentrations for non-high-density lipoprotein (nonHDL) apoC-III in men and women were 6.4 and 6.2 mg/dl, respectively, and for apoC-III in HDL were 6.2 and 6.3 mg/dl, respectively. NonHDL apoC-III was similar to, and apoC-III in HDL was higher than that in Western populations. Both fractions of apoC-III were significantly correlated with lipids, lipoproteins, apoB, anthropometric measures, and blood pressures in both genders. Correlations for both were high with serum triglycerides (r(s) = around 0.70) and apoB (r(p) = around 0.37). Total apoC-III as well as both fractions were significantly correlated in women also with levels of inflammatory risk markers: strongly (r = 0.40-0.45, P 7.0 mg/dl as opposed to lower levels of nonHDL apoC-III indicated the presence of hypertriglyceridemic hyperapo B with an age-adjusted odds ratio (OR) of 13.8; it indicated the presence of metabolic syndrome with 4.66-fold likelihood. Total apoC-III and nonHDL apoC-III proved to be significantly (P-trend < 0.05 and 0.002) and strongly associated with prevalent CHD in men even after adjustment for age, low-density lipoprotein-cholesterol (LDL-C) and high-density lipoprotein-cholesterol (HDL-C): OR gradients across upper and lower quartiles were 3.88-fold (CI: 1.3; 11.4) and 8.8-fold (CI: 2.6; 29.8), respectively. Conclusions: In a population among whom the metabolic syndrome prevails, total- and nonHDL apoC-III are each a determinant in both genders of the metabolic syndrome and of hypertriglyceridemic hyperapo B. Each is a powerful significant marker of prevalent CHD in men independent of LDL- and HDL-C levels. In women, despite being correlated with inflammatory risk markers, the significant association of elevated levels of apoC-III with CHD did not prove to be independent of age. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: apolipoprotein C-III; coronary heart disease; high-density lipoprotein; metabolic syndrome; triglyceride-rich lipoproteins; POSTPRANDIAL TRIGLYCERIDE; LIPASE ACTIVITY; APOC-III; PLASMA; MODULATION; BINDING; LIPIDS; CHOLESTEROL; POPULATION; Cardiovascular System & Cardiology